Kegiatan Pembuatan Mural di TK Khalifah III Kebon Raja sebagai Upaya Peningkatan Lingkungan Belajar Anak Usia Dini - Husnus Sawab; Ria Purnama; Karima Adilla; Ulfa Mazaya; Sri Batara Nurfajri Arisaputri; Atika Aditya; Dyah Erti Idawati; Siti Zahrina Fakhrana (Universitas Syiah Kuala, 2026)
An engaging and stimulating learning environment plays a crucial role in supporting the cognitive and emotional development of early childhood learners. However, many early childhood education facilities still lack educational visual elements within their learning and play spaces. This community service activity aims to enhance the quality of the learning environment through the implementation of an educational mural at TK Khalifah III Kebon Raja, Banda Aceh. The method consisted of several stages, including preliminary observation of the school environment, mural concept design, preparation of tools and materials, painting implementation, and evaluation of the outcomes. The mural concept adopted a marine life theme, featuring illustrations of sea organisms, the use of bright colors, and visually engaging educational elements suitable for children. The results indicate that the mural significantly improved the aesthetic quality of the play area while also creating a more communicative and enjoyable visual learning medium for students. The previously monotonous environment was transformed into a more vibrant and interactive space. In addition, the activity provided experiential learning opportunities for students involved in the design and implementation process. Positive responses from both teachers and students demonstrate that murals function not only as decorative elements but also as effective educational media in supporting early childhood learning. Therefore, the application of educational murals can be considered a simple yet impactful design intervention to improve the quality of educational environments